Yield Response And Water Productivity For Rice Growth With Several Irrigations Treatment In West Java - Hendri Sosiawan; Wahida Annisa (Program Pascasarjana Universitas Sriwijaya, 2019)
As the challenges toward increasing water for irrigation and water scarcity threats become more prevalent, knowledge of crop yield response to water can facilitate the development of irrigation strategies for improving agricultural productivity. Experiments were conducted to to compare water usage of several irrigation treatment on rice growth performance and productivity and its water use efficiency. These experiments were conducted using Situbagendit rice variety (115 day length periode), Urea and Tri Super Phospate fertilizer. Fertilizer dosage follows fertilizer recommendations for rice, i.e : Urea 250 kg/ha, SP-36 100 kg/ha and 100 kg KCl/ha. Irrigation started from land preparation. controll block (deep flooding) was flooded by a water height of 7 cm. Low level continues flow block was flooded by a water height of 3-5 cm. The volume of water used to saturate the soil of the saturated block was estimated. The number of days of non-flooded soil in AWD before irrigation is applied can vary from 1 day to more than 5 days. The results showed that total volume of water supplied during the rice growing period in the control block was 2,761.91 m3. Total water volume related to the low level continous flow irrigation block was about 1,217.03 and only about 638.98 m3 for the alternate wet and dry irrigation block. Total volume supplied for soil saturation treatment was about 549.74 m3. Regardless the performance of rice crop growth, it’s the most efficient treatment in terms of water use. It only required an amount of water around14-20 % of amount of water consumed by the continuous deep flooding treatment. The rice yield of deep flooding irrigation treatment was equivalent to 5.6 tons/ha of dry paddy while the yields of low level continuous flow irrigation,alternate wet and dry irrigation and soil saturation treatments reached 5,3 tons/ha,3.36 tons/ha and 2.80 tons/ ha respectively